Clinical Legal Education for Human Rights Issues: How Students Can Implement Their Basic Knowledge of Human Rights in Reality - Arifin, Ridwan (The Indonesian Journal of International Clinical Legal Education, 2019)
Human rights was recognized as a fundamental issue both internationalcommunity and regional community like ASEAN. The student capabilityto transfer their knowledge concerning to the human rights wasbecome very important thing for legal development as well as lawenforcement. Through clinical legal education, students were beprepared to be available bring a justice in their real lives. Clinical legaleducation which specifically for human rights issues prepares studentfor lifelong careers in social justice advocacy around the globe. Throughthe Clinic, students join a community advocates working to promotehuman rights and recalibrate the global power imbalances that driveeconomic and political inequity, exploitation, threats to physicalsecurity, poverty, and environmental injustice. Through fact-finding,reporting, litigation, media engagement, advocacy, training, andinnovative method, the Clinic seeks to prevent abuse, advance respectfor human rights, and promote accountability for violations. The paperdivided into three main folds, first, how was the human rights issues onclinical legal education in some practices, second, how was the studentencourage the basic knowledge of human rights through clinical legaleducation, and three, how was the student use their knowledge in theirreality lives. The paper emphasized that, at the intersection of theoryand practice, the Clinic can be used as a laboratory for testing andmodeling new and innovative modes of human rights work, and seeksto be a model of rigorous and critical human rights advocacy. Thisincludes a focus on enhancing human rights methods throughinterdisciplinary partnerships, critical reflection on human rightspractice, and sustainable advocacy through attention to vicarioustrauma and resilience.